1997
DOI: 10.1046/j.1471-4159.1997.69052026.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Tau by Lysosomal Enzyme Cathepsin D: Implication for Alzheimer Neurofibrillary Degeneration

Abstract: The degradation of different isoforms of human recombinant tau (R‐tau; T39, T40, and T44) and fetal tau (F‐tau) by cathepsin D (CD) was investigated. Gel electrophoresis and Coomassie Blue staining of different R‐tau species digested at pH 3.5 showed very little differences in CD susceptibility. Immunoblotting analyses revealed that amino and carboxy termini of tau were cleaved before other regions. F‐tau was most vulnerable to proteolysis at both termini. Digestion of R‐tau with 0.01 unit of CD/ml at pH 3.5 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 39 publications
3
133
0
Order By: Relevance
“…26,27 In light of those findings, and because cat D released from lysosomes is exposed to a higher pH in the cytosol, we felt that it was important to determine whether cat D could induce apoptosis at pH values higher than 5.5. Our results indicate that cat D also induces apoptosis at pH 7.0, and therefore it might be able to proteolytically cleave substrates outside the lysosomal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In light of those findings, and because cat D released from lysosomes is exposed to a higher pH in the cytosol, we felt that it was important to determine whether cat D could induce apoptosis at pH values higher than 5.5. Our results indicate that cat D also induces apoptosis at pH 7.0, and therefore it might be able to proteolytically cleave substrates outside the lysosomal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…CD is optimally active against most substrates at pH 3 to 4. However, CD is able to cleave Bid at pH 6.2 and tau protein at pH 7 in vitro [57,69]. Bidere et al found that Bafilomycin A, an inhibitor of lysosomal acidification, did not inhibit CD mediated apoptosis of T lymphocytes induced by staurosporine.…”
Section: Apoptosismentioning
confidence: 99%
“…The CD level also increases in cerebrospinal fluid [137][138][139][140][141]. CD has been implicated in the processing of amyloid precursor protein (APP) [56], apolipoprotein E (apoE) [61] and the tau protein [57], which are important factors of AD pathogenesis [136,142]. However, the study of CD-knockout mice revealed that CD is not essential for APP processing [143].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In support, (1) endolysosomes are the major site, where Aβ is produced [52,53], and endolysosome dysfunction leads to brain deposition of Aβ [17]; (2) Endolysosomes are responsible for synaptic protein recycling [54][55][56], and endolysosome dysfunction leads to disruption of synaptic integrity in brain [57][58][59][60][61]; (3) Tau can be degraded by cathepsin D in autophagosomes-lysosomes [62][63][64][65] and increased levels of endolysosome cholesterol, as occurs in Niemann-Pick type C disease, leads to lysosome dysfunction and tau-pathology [66][67][68][69][70][71]. Substantial evidence from human epidemiological studies and from experimental studies conducted in animals and cultured cell models indicate that caffeine, when ingested chronically, can decrease Aβ levels, protect against the onset and severity of AD, and in some cases it can reverse behavioral and pathological features of AD [19,21,24,29].…”
Section: Discussionmentioning
confidence: 99%